UPAYA PENGENDALIAN RISIKO BAHAYA PRAKTIKUM DESAIN FABRIKASI PELAT MENGGUNAKAN JOB SAFETY ANALYSIS (JSA) - Erniyani, Erniyani; Nurfuadah, Nurfuadah; Ramdhani, Irin; Raodah, Raodah; Hasbullah, Hasbullah (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
Occupational safety and health have a major role in organizations. Occupational safety and health (K3) is a supporting factor for the productivity of an organization. One of the activities with potential danger is in the laboratory which can endanger practitioners during the teaching and learning process due to non-compliance with occupational safety and health (K3) procedures. Such as welding a work object without wearing glasses, thereby potentially being exposed to flames. The plate fabrication design laboratory majoring in mechanical engineering education has many activities carried out, namely cutting workpieces, welding, soldering, etc. Therefore, as an effort to eliminate the risk of work accidents in the laboratory, job safety analysis (JSA) is implemented. The implementation of JSA gives workers a sense of security when working because they can know the dangers that exist in a job so they can take control measures and increase awareness of the importance of K3. Increasing K3 knowledge using Job Safety Analysis (JSA) plays a role in eliminating dangers in the workplace so that work accidents can be prevented. The research results show that the greatest priority risks are in the cutting and welding process, such as injuries caused by sharp objects, exposure to heat, and the presence of sparks. So risk mitigation is needed so that practicum implementation remains safe and efficient.